Pengaruh Penerimaan Teknologi dengan Kebergunaan Web:: Studi Kasus Portal Rumah Belajar Kemendikbud - M. Hasan Chabibie; Wildan Hakim (Universitas Multimedia Nusantara, 2016)
The availability of internet service in Indonesia has enabled online learning. Through the portal provided by the Indonesian Ministry of Education and Culture (http://belajar.kemdikbud.go.id), internet user from all backgrounds can access various learning materials. Rumah Belajar portal is an online learning media which purposively developed for teachers and students to easily access learning materials. This portal facilitates interactivity between teachers and students with the portal. Through this portal, students and teachers can access learning materials, perform interactive simulation, communicate and interact with education communities. This research aims to explore the influence of technology acceptance on the usability of Rumah Belajar portal. The result shows a strong relation between internet technology acceptance as learning media by user and the goal and attitude of informants in accessing the portal. The user perception on the usability of Rumah Belajar portal has a close correlation with satisfaction, download delay, and the content. Keywords: Information acceptance, technology accpetance, web usability, Rumah Belajar portal user satisfaction